2013
DOI: 10.1371/journal.pone.0059696
|View full text |Cite|
|
Sign up to set email alerts
|

Foxp3 (−/ATT) Polymorphism Contributes to the Susceptibility of Preeclampsia

Abstract: ObjectiveTo evaluate the potential influence of Foxp3 polymorphism on preeclampsia (PE) susceptibility, we conducted a case-control study in Han Chinese women.Methods Foxp3 genotyping was determined by polymerase chain reaction with sequence-specific primers (PCR-SSP) in 156 PE patients and 252 age-frequency matched controls. Immunohistochemical staining was used to detect the expression of Foxp3 specific transcription factor in 30 PE and 30 normal pregnant women.ResultsThe positive rate of Foxp3 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 15 publications
3
40
1
Order By: Relevance
“…31 On the other hand, the two Foxp3 polymorphisms (rs2232365 and rs3761548) proved to be significantly associated with RPL. This result consolidates the findings of Chen et al, (2013) and Wu et al, (2011) who reported significant associations between pre-eclampsia and rs3761548 in Indian women and between the two polymorphisms and unexplained RPL in Chinese women. 32 In the contrary, Abbasirad et al, (2013) Discrepancies between results of genetic association studies like those encountered here could be due to many reasons including population genetic variation (background) unrelated to the investigated alleles, presence of nucleotide polymorphism somewhere else in the examined gene e.g., in the coding/non-coding regions, epigenetic alterations and linkage disequilibrium to other sequence variants in the vicinity of the studied loci.…”
Section: Discussionsupporting
confidence: 91%
“…31 On the other hand, the two Foxp3 polymorphisms (rs2232365 and rs3761548) proved to be significantly associated with RPL. This result consolidates the findings of Chen et al, (2013) and Wu et al, (2011) who reported significant associations between pre-eclampsia and rs3761548 in Indian women and between the two polymorphisms and unexplained RPL in Chinese women. 32 In the contrary, Abbasirad et al, (2013) Discrepancies between results of genetic association studies like those encountered here could be due to many reasons including population genetic variation (background) unrelated to the investigated alleles, presence of nucleotide polymorphism somewhere else in the examined gene e.g., in the coding/non-coding regions, epigenetic alterations and linkage disequilibrium to other sequence variants in the vicinity of the studied loci.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, studies have shown that polymorphisms in those genes are associated with various inflammatory and autoimmune diseases, such as rheumatoid arthritis, multiple sclerosis and SLE, that may also predispose to RPL [3,8,9,[18][19][20][21]. However, very limited studies, and for NKG7 no previous studies, have investigated the direct relation between those five polymorphisms and unexplained RPL.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, studies in autoimmunity should be stratified based on gender . In addition, the role of FOXP3 variants has been evaluated in many female immune‐related disorders such as unexplained recurrent spontaneous abortion and preeclampsia . Furthermore, there are few reports indicating the protective role of some FOXP3 variants against autoimmune disorders such as vitiligo or allergic rhinitis in only female patients or a more pronounced effect of some variants in male patients, which implies a distinct sex‐related pathogenesis for such disorders.…”
Section: Discussionmentioning
confidence: 99%